o valor da expresão abaixo,quando a=6 e b=9,è
![\sqrt[3]{b-a²} \sqrt[3]{b-a²}](https://tex.z-dn.net/?f=+%5Csqrt%5B3%5D%7Bb-a%C2%B2%7D+)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
• ³√b-a²
} sendo a = 6 e b = 9
• ³√9-6²
} 6² = 6.6 = 36
• ³√9-36
• ³√-27
} ³√-27 = -3 ,pois (-3)³ = (-3.-3.-3) = -27
} -3*
Espero ter ajudado...obgd...
Perguntas interessantes
Matemática,
8 meses atrás
Inglês,
8 meses atrás
Biologia,
8 meses atrás
Matemática,
10 meses atrás
Geografia,
10 meses atrás
Matemática,
1 ano atrás
História,
1 ano atrás